PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Safitri, 15.05.52.0094; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of profitability, company size, sales growth, and leverage on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The independent variable of this study consisted of profitability, company size, sales growth, and leverage, while the dependent variable in this study was tax avoidance. This study uses secondary data. The sampling technique in this study was purposive sampling and the data analysis tool used was descriptive statistics, normality test, multicollinearity test, autocorrelation, heteroscedasticity test, multiple linear regression analysis, test coefficient of determination, F test, t test using SPSS 25 for window. The results showed that profitability and sales growth did not affect tax avoidance, while firm size and leverage affected tax avoidance.